Passive cooling energy systems SWOT analyses for energy-use reductions at three spatial levels - Dawodu, Ayotunde; Cheshmehzangi, Ali (Elsevier, 2017)
Passive cooling energy systems are significantly important in achieving efficient design and performative built environment. Encouragingly, there are many passive cooling energy systems at three spatial levels of macro, meso and micro. In this research study, these energy systems are identified and are assessed in a SWOT analysis evaluation. Apart from social and economic implications that are broad and effective for most of passive cooling energy systems, this study focuses on the energy systems’ implications across five indicators of practice, health, environment, energy and policy, which are significant for disciplines of sustainable energy systems and the built environment. This study aims to evaluate the interdependency of each indicator across three spatial levels and then argue for methods that can be considered for potential implementation of passive cooling energy systems. Furthermore, this study offers a holistic overview of all available passive cooling energy systems and argue based on interplay between five indicators across the three studied spatial levels. This study focuses on warmer climate zones (e.g. hot and dry; hot and humid), where passive cooling is expected to me more effective and obligatory. As a result, this study aims to help energy specialists, policy makers, planners and designers to evaluate how they can utilize passive cooling energy systems based on the key studied indicators. Finally, this paper gives an overview of gaps in policy and practice implementation of such systems in practice and their effectiveness at various spatial levels of the built environment.